The brazilian telenovelas and Mikhail Bakhtin: an analysis of outsideness, authorship, and speech genres - Lopes da Silva, Anderson (2021)
This essay discusses the concepts of outsideness, authorship, and speech genres in the study of Brazilian telenovelas (soap operas). Its empirical object of analysis is Cordel Encantado (The Enchanted Tale), a melodrama produced and exhibited in 2011 by Rede Globo de Televisão in Brazil. Furthermore, Mikhail Bakhtin’s thinking is conducted by the conceptual tension of excess of seeing, author-creator, author-person, and secondary speech genres (analyzed within the scope of television fiction). Finally, it is possible to affirm that Mikhail Bakhtin’s dialogism (when specifically relocated inside mass media) reveals how the ideas of authorship and discourse are resignified in the complex melodramatic fabric of the Brazilian telenovela.